Pengaruh Tekanan Sosial dan Budaya Organisasi Terhadap Budgetary Slack dengan Religiusitas Sebagai Pemoderasi - Rizky Budi Darmawan; Supramono; Indarto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The problem that arises is Budgetary slack in the DPUPR of Grobogan Regency for the past few years. This can occur allegedly due to social pressure and organizational culture that can influence Budgetary slack. Therefore, from the background above, the author wants to re-examine the influence of social pressure and organizational culture related to budget preparation that creates budget slack. The purpose of this study is to analyze the influence of social pressure and organizational culture related to budget preparation that creates budget slack with religiosity as a moderator. The population used in this study were all employees of the Public Works and Spatial Planning Agency of Grobogan Regency, totaling 86 people. The sample selection used purposive sampling. The sample used was 72 employees of the Public Works and Spatial Planning Agency of Grobogan Regency. The analysis tool used is the quantitative analysis method, namely structural equation modeling. Based on the results of the study, social pressure and organizational culture have a positive and significant effect on Budgetary slack. Religiosity moderates the influence of social pressure and organizational culture on Budgetary slack.